Learning cum Development Outcomes and Training Budget of Technology Based Entrepreneurial Firms in a Recessive Economy - Akinbola Omolola Sariat & Badewole Oluwatimilehin Adesubomi, Akinbola Olufemi Amos, Kowo Solomon Akpoviroro (Covenant Journal of Entrepreneurship, 2019)
Learning and development outcomes in organizations have been of contention in most technology based entrepreneurial firms in recessive economies like Nigeria and the inability to appropriate finance for learning and development priorities tend to inhibit the growth of human capital in the nation’s economy at large. The research analyzed the effect of operation budget on learning effectiveness during recession and evaluated the effect static budget on competitive advantage during recession. The findings showed that operation budget have significant effect on learning effectiveness (at P =0.004). It was also found that static budget does not have any significant relationship with competitive advantage (at P= 0.084). The research concludes that economic meltdown has not too many effects on learning and development outcomes of human capital as organizations still gets value for trainings on employee with reference to productivity in Nigeria. The study further recommends that entrepreneurial firms should create enabling operating environment for employees through right learning and development policies to avoid degradation of human capital.